Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) Pada Dinas Komunikasi, Informatika dan Statistik Provinsi Lampung Dengan Prinsip Good Governance - Aulia Fitri, Anisa; Ridlwan, Zulkarnain; Natamiharja, Rudi (Universitas Ekasakti, 2024)
The aim of this research is to analyze the implementation of SPBE in the Lampung Province Communication, Informatics and Statistics Service and analyze the suitability of the SPBE implementation in the Lampung Province Communication, Informatics and Statistics Service with the principles of good governance. This type of research is normative-empirical legal research, using primary data and secondary data. The research approach uses a statutory-regulatory approach (legislative approach) and a contextual approach (conceptual approach). The results of this research show that the implementation of SPBE in the Communication, Informatics and Statistics Service of Lampung Province obtained an index of 3.37 or was included in the good predicate according to data from evaluation results by the Ministry of State Apparatus Empowerment and Bureaucratic Reform in 2023. In detail, namely the policy domain with an index of 4.70, the governance domain manage with an index of 3.30, management domain with an index of 1.64, and service domain with an index of 3.63. This is in accordance with William Chamblis and Robert B. Seidman's Law Writing Theory, namely that the Lampung Provincial Government is the law-making institution that applies the Lampung Governor's Regulation on SPBE. The operation of the law in accordance with this regulation concerns the existence of other forces (parties) outside the provincial government, namely SPBE users from central agencies, State Civil Service employees, individuals, communities, business actors and other parties. The implementation of SPBE in Lampung Province is in line with 8 (eight) principles of good governance and in accordance with the Good Governance Theory, namely the implementation of SPBE meets legal certainty based on regulations at both the central and regional levels, the implementation of SPBE fulfills the principle of benefit for its users, impartiality in the implementation of the Lampung Governor's Regulation on SPBE, the SPBE application providing careful services to its users, regional officials not abusing their authority in the SPBE application, openness/transparency in the implementation of SPBE, containing the public interest, and good service to the community. The implementation of SPBE in Lampung Province is still faced with obstacles, namely the management domain which is still in the deficient category, there is still a lack of public understanding about SPBE and the uneven distribution of SPBE to all State Civil Apparatus (ASN) in Regional Apparatus Organizations (OPD) within the Lampung Provincial Government.